2017
DOI: 10.1016/j.virol.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization, molecular epidemiology, and phylogenetic relationships of insect-specific viruses in the taxon Negevirus

Abstract: The recently described taxon Negevirus is comprised of a diverse group of insect-specific viruses isolated from mosquitoes and phlebotomine sandflies. In this study, a comprehensive genetic characterization, molecular, epidemiological and evolutionary analyses were conducted on nearly full-length sequences of 91 new negevirus isolates obtained in Brazil, Colombia, Peru, Panama, USA and Nepal. We demonstrated that these arthropod restricted viruses are clustered in two major phylogenetic groups with origins rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 58 publications
(91 reference statements)
10
116
0
Order By: Relevance
“…Negevirus ORF1 (756 bp) phylogenetic analysis revealed a major split in two groups, named Nelorpivirus and Sandewavirus , with a different ancestral origin, corroborating previous observations indicating that geography may also play a role in Negevirus evolution and sub‐speciation (Nunes et al , ). Santana and Siriri viruses formed a cluster inside Sandewavirus subgroup, very close to other negeviruses identified in mosquitoes worldwide (Vasilakis et al , ; Kallies et al , ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Negevirus ORF1 (756 bp) phylogenetic analysis revealed a major split in two groups, named Nelorpivirus and Sandewavirus , with a different ancestral origin, corroborating previous observations indicating that geography may also play a role in Negevirus evolution and sub‐speciation (Nunes et al , ). Santana and Siriri viruses formed a cluster inside Sandewavirus subgroup, very close to other negeviruses identified in mosquitoes worldwide (Vasilakis et al , ; Kallies et al , ).…”
Section: Discussionsupporting
confidence: 87%
“…quinquefasciatus in tropical regions (Bittar et al , ). Moreover, the cysteine residues and potential glycosylation sites found in CxFV sequences in the present study are associated with genomic secondary structure maintenance, pathogenicity and viral infectivity in their hosts (Murrell et al , ; Nunes et al , ).…”
Section: Discussionmentioning
confidence: 68%
“…Negevirus was recently described as a diverse group of ISVs isolated from mosquitoes and phlebotomine sandflies [30]. In this study, two novel negevirus-like sequences were found in C. vishnui subgroup mosquitoes.…”
Section: Negevirus-related Virusesmentioning
confidence: 63%
“…Even when sequencing discrete organisms such as a singular honeybee, the co-existence of eukaryotic parasites means that imputation of viral host cannot be exact (Runckel et al, 2011). Host promiscuity seems to be a common theme among newly-described RNA viruses (Nunes et al, 2017). Highly-indexed libraries, chemical linkage of RNA species, and physical partitioning through single cell transcriptomics currently provide the best potential solution to the host imputation problem in complex mixtures (Burton et al, 2014;Chow et al, 2015;Turner et al, 2009).…”
Section: Easier Faster Better Broader Protocolsmentioning
confidence: 99%